2022
DOI: 10.3390/nano12132183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biosynthesized Silver Nanoparticles on Bacterial Biofilm Changes in S. aureus and E. coli

Abstract: One approach for solving the problem of antibiotic resistance and bacterial persistence in biofilms is treatment with metals, including silver in the form of silver nanoparticles (AgNPs). Green synthesis is an environmentally friendly method to synthesize nanoparticles with a broad spectrum of unique properties that depend on the plant extracts used. AgNPs with antibacterial and antibiofilm effects were obtained using green synthesis from plant extracts of Lagerstroemia indica (AgNPs_LI), Alstonia scholaris (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“…AgNPs had little impact on the biofilm that Gram-negative bacteria formed; their values ranged from 22 to 40.17 mm. Nonetheless, our biosynthesized silver nanoparticles were not as effective against the tested Gram-positive bacteria’s biofilm; 64.85 and 59.13% of the inhibitory effect on biofilm were found against Candida albicans and Candida sake , respectively; the maximum inhibitory effect was found against Candida species [ 71 ]. The high biofilm-suppression activity of silver nanoparticles was demonstrated against S. aureus , Bacillus subtilis , and Pseudomonas aeruginosa [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…AgNPs had little impact on the biofilm that Gram-negative bacteria formed; their values ranged from 22 to 40.17 mm. Nonetheless, our biosynthesized silver nanoparticles were not as effective against the tested Gram-positive bacteria’s biofilm; 64.85 and 59.13% of the inhibitory effect on biofilm were found against Candida albicans and Candida sake , respectively; the maximum inhibitory effect was found against Candida species [ 71 ]. The high biofilm-suppression activity of silver nanoparticles was demonstrated against S. aureus , Bacillus subtilis , and Pseudomonas aeruginosa [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…18 The inhibitory effect of AgNPs on biofilm formation in vitro may depend on the size, concentration, and stability of the nanoparticles, as well as the specific bacterial species involved. 19,20 The present study is a continuation of our systematic study of a newly revealed phenomenon of the drop in antibiotic resistance caused by therapy with Argovit-C AgNP formulation. 19,21−24 In the previous works, we revealed that the reasons for the drop in antibiotic resistance after the animal therapy with Argovit-C AgNP formulation were caused by the decrease in antibiotic efflux by bacteria, 19,22−24 the drop of bacterial adhesion to the cells, and the diminishment in bacteria antilysozyme activity.…”
Section: ■ Introductionmentioning
confidence: 86%
“…AgNPs can disrupt the integrity of bacterial cell membranes and interfere with cellular processes, making them effective at preventing biofilm formation and eradicating existing biofilms . The inhibitory effect of AgNPs on biofilm formation in vitro may depend on the size, concentration, and stability of the nanoparticles, as well as the specific bacterial species involved. , …”
Section: Introductionmentioning
confidence: 99%
“…Thus, these diverse bioactive compounds make L. indica an ideal choice for nanoparticle synthesis. Several studies have examined the impact of biosynthesized silver nanoparticles on altering bacterial biofilms in both gram-negative and gram-positive bacteria [ 59 ], as well as investigating the anticancer, antimicrobial, and hemolytic properties of zinc oxide nanoparticles [ 60 ], using leaf extracts from L. indica . However, the potential of employing L. indica leaf extract in the synthesis of CuO NPs with multiple functionalities remains unexplored.…”
Section: Introductionmentioning
confidence: 99%